2016
DOI: 10.1103/physrevb.93.174304
|View full text |Cite
|
Sign up to set email alerts
|

Broad-angle negative reflection and focusing of elastic waves from a plate edge

Abstract: Guided elastic waves in plates, or Lamb waves, generally undergo reflection and mode conversion upon encountering a free edge. In the case where a backward-propagating Lamb wave is mode-converted to a forwardpropagating wave or vice versa, the mode-converted wave is reflected on the same side of the surface normal as the incident wave. In this paper, we study such negative reflection and show that this effect can be achieved over a broad angular range at a simple plate edge. We demonstrate, through both numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In a pionneering experiment, few years ago, Germano et al showed that this conversion from forward to backward Lamb waves also occurs at a simple free edge of an elastic plate, giving rise to negative reflection [18]. More recently, in a concurrent study by Veres et al , the negative reflection of Lamb waves has been investigated above the ZGV resonance through numerical simulations and laser-ultrasound experiments [19].…”
Section: Introductionmentioning
confidence: 99%
“…In a pionneering experiment, few years ago, Germano et al showed that this conversion from forward to backward Lamb waves also occurs at a simple free edge of an elastic plate, giving rise to negative reflection [18]. More recently, in a concurrent study by Veres et al , the negative reflection of Lamb waves has been investigated above the ZGV resonance through numerical simulations and laser-ultrasound experiments [19].…”
Section: Introductionmentioning
confidence: 99%
“…The randomly disordered slab can therefore act as a band gap material. The observation of such super-focusing phenomena would require an experiment with an extremely fine frequency tuning 42 . Moreover, it should also involve a non-invasive point-like source capable of a selective excitation of the forward or backward mode.…”
Section: Discussionmentioning
confidence: 99%
“…NR is therefore a very general phenomenon and this work can be, in principle, transposed to all the aforementioned systems. In this article, we have chosen to consider the NR of elastic waves in plates because they provide an excellent platform to investigate negative refraction [38][39][40] and reflection [41][42][43] . Indeed, laser interferometry allows to probe the wave-field over the whole plate surface with an excellent spatial, temporal and spectral resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Such zero group velocity (ZGV) points exhibit a strong resonance that can be efficiently generated with a laser excitation source, and they have been used for a variety of applications in the nondestructive evaluation of materials [5][6][7][8][9]. In addition, it has been demonstrated that the mode conversion between backward and forward propagating Lamb waves at a thickness step in a plate or at a plate edge gives rise to non-intuitive effects such as negative refraction and negative reflection [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%